2002
DOI: 10.1172/jci0215272
|View full text |Cite
|
Sign up to set email alerts
|

Myeloerythroid-restricted progenitors are sufficient to confer radioprotection and provide the majority of day 8 CFU-S

Abstract: Whole-body irradiation at the minimal lethal dose causes bone marrow failure and death within 12-18 days. To identify the principal components of the hematopoietic system that are radioprotective, we transplanted lethally irradiated mice with purified progenitors: common myeloid progenitors (CMPs), megakaryocyte/erythrocyte-restricted progenitors (MEPs), or granulocyte/monocyte-restricted progenitors (GMPs). Transplanted CMPs gave rise to cells both of the granulocyte/monocyte (GM) series and the megakaryocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(92 citation statements)
references
References 38 publications
4
88
0
Order By: Relevance
“…Importantly, we also observed donor contribution to megakaryocyte progenitors (MkPs: lin − c-kit + Sca1 − CD41 + ), and erythroid progenitors (EPs: lin − ckit + Sca1 − Endoglin + ) demonstrating that the reconstituting cells were able of give rise to precursor cells of platelets and erythrocytes. Radioprotection transplantation assays performed using donor-derived MEPs (Na Nakorn et al, 2002) confirmed that the reprogrammed cells possessed a robust ability to generate platelets and red blood cells in vivo (Figure S4C–D). Importantly, subfractionation of the LSK compartment revealed donor-derived reconstitution of the multi-potent progenitor (MPP1: lin − ckit + Sca1 + CD34 + Flk2 − , MPP2: lin − c-kit + Sca1 + CD34 + Flk2 + ) and HSC (lin − c-kit + Sca1 + CD34 − Flk2 − ) compartments (Figure 5C–D, F).…”
Section: Resultsmentioning
confidence: 86%
“…Importantly, we also observed donor contribution to megakaryocyte progenitors (MkPs: lin − c-kit + Sca1 − CD41 + ), and erythroid progenitors (EPs: lin − ckit + Sca1 − Endoglin + ) demonstrating that the reconstituting cells were able of give rise to precursor cells of platelets and erythrocytes. Radioprotection transplantation assays performed using donor-derived MEPs (Na Nakorn et al, 2002) confirmed that the reprogrammed cells possessed a robust ability to generate platelets and red blood cells in vivo (Figure S4C–D). Importantly, subfractionation of the LSK compartment revealed donor-derived reconstitution of the multi-potent progenitor (MPP1: lin − ckit + Sca1 + CD34 + Flk2 − , MPP2: lin − c-kit + Sca1 + CD34 + Flk2 + ) and HSC (lin − c-kit + Sca1 + CD34 − Flk2 − ) compartments (Figure 5C–D, F).…”
Section: Resultsmentioning
confidence: 86%
“…CFU-S colonies that originate from myeloerythroid-restricted progenitors are known to protect against WBI-induced lethality [25], presumably by allowing time for more primitive stem cells to develop. These are likely related to cells of the promyelocytic and neutrophilic myelocytic lineage that are found in the blood of all species studied within hours of WBI in the lethal range [16].…”
Section: Resultsmentioning
confidence: 99%
“…Myeloid cells have long been associated with hARS [19], giving rise to CFU-S on day 8–10 that protect against WBI lethality until such times as the pluripotent hematopoietic stem cell pool recovers [25]. Our observation on the emergence of CD11b + Ly6C + Ly6G + myeloid cells in bone marrow and peripheral organs soon after WBI is in accord with previous early observations that “neutrophilia” is one of the earliest responses to potentially lethal WBI, which is thought to be related to later (day 4–14) “abortive” rises in cells of this series [16] and CFU-S formation [25]. The drug is known to activate the Wnt pathway in various cells in vitro (Pajonk, in preparation), while in vivo the compounds increase this myeloid response which is essential for hARS mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mice undergoing hematopoietic recovery produce primarily myeloerythroid cells, and myeloerythroid-restricted progenitors are sufficient to confer radioprotection (Uchida et al, 1994; Na Nakorn et al, 2002). We further characterized the bone marrow colonies by IHC staining for the erythroid marker TER-119 (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%